AMIODARONE PROPHYLAXIS FOR ATRIAL FIBRILLATION AFTER CORONARY ARTERY BYPASS GRAFTING: Amiodarone Prophylaxis for Atrial Fibrillation - Naqvi, Shahab; Hussain, Syed Aqeel (Pakistan Armed Forces Medical Journal, 2008)
Objective: This study was planned to evaluate the preventive role of Amiodarone against atrial fibrillation after coronary artery bypass grafting.Design: A comparative and interventional study.Place and Duration of Study: The study was done at Armed Institute of Cardiology/National Institute of Heart Diseases AFIC/NIHD Rawalpindi.Patients and Methods: In this study, 100 patients admitted three days before coronary artery bypass grafting were divided into Control and Amiodarone groups of 50 patients each. Patients in Control group did not receive any prophylaxis against atrial fibrillation before and after the coronary artery bypass grafting. While the patients in Amiodarone group received 200 mg oral Amiodarone thrice daily for three days, then 200 mg once daily on operative day and continued so until discharge.Results: Postoperative atrial fibrillation occurred in 8 of 50 patients in the Control group (16%) and 2 of 50 patients in the Amiodarone group (4%) (p=0.045). Maximum ventricular rate during atrial fibrillation episode in Control group was 122 ± 5.83 beats per minute and 108 ± 2.89 beats per minute in amiodarone group. Conclusion: Preoperative amiodarone was found to be significantly useful prophylactic agent to prevent atrial fibrillation after coronary artery bypass grafting and this drug can be used safely.